Infeksi Alami Pepper Yellow Leaf Curl Virus dan Sweet potato virus C Pada Ubi Jalar di Malang, Jawa Timur - Tri Asmira Damayanti; Anastasya Hondo; Yusmani Prayogo (Jurnal Fitopatologi Indonesia, 2019)
Virus-like infection with vein yellowing and leaf malformation symptoms were observed on sweet potato IR Melati at Kendalpayak, Malang, East Java. Amplification of DNA/cDNA was carried out using universal primer of Begomovirus, Potyvirus and Cucumovirus showed successfully amplified by universal primer of Begomovirus and Potyvirus, while negatively to universal primer of Cucumovirus. Based on nucleotide sequences, the vein yellowing and leaf malformation symptoms on sweet potato caused by double infection of Pepper yellow leaf curl virus (PYLCV) and Sweet potato virus C (SPVC). DNA identity analysis using BioEdit software showed highest homology up to 98.5% to one of PYLCV isolates from Bali, and up to 98.0% to sweet potato isolate of SPVC from Japan and USA. This is a new finding of natural infection of PYLCV and SPVC on sweet potato in Indonesia.